# properties of set difference

Let $A,B,C,D,X$ be sets.

1. 1.

$A\setminus B\subseteq A$. This is obvious by definition.

2. 2.

If $A,B\subseteq X$, then

 $A\setminus B=A\cap B^{\complement},\qquad(A\setminus B)^{\complement}=A^{% \complement}\cup B,\qquad\mbox{and}\qquad A^{\complement}\setminus B^{% \complement}=B\setminus A$

where ${}^{\complement}$ denotes complement  in $X$.

###### Proof.

For the first equation, see here (http://planetmath.org/PropertiesOfComplement). The second equation comes from the first: $(A\setminus B)^{\complement}=(A\cap B^{\complement})^{\complement}=(A^{% \complement})\cup(B^{\complement})^{\complement}=A^{\complement}\cup B$. The last equation also follows from the first: $A^{\complement}\setminus B^{\complement}=A^{\complement}\cap(B^{\complement})^% {\complement}=B\cap A^{\complement}=B\setminus A$. ∎

3. 3.

$A\subseteq B$ iff $A\setminus B=\emptyset$.

###### Proof.

Since $A\subseteq B$, $B^{\complement}\subseteq A^{\complement}$. Then $A\setminus B=A\cap B^{\complement}\subseteq A\cap A^{\complement}=\emptyset$. On the other hand, suppose $A\setminus B=\emptyset$. Then $A\cap B^{\complement}=\emptyset$ by property 1, which means $A\subseteq(B^{\complement})^{\complement}=B$. ∎

4. 4.

$A\cap B=\emptyset$ iff $A\setminus B=A$.

###### Proof.

Suppose first that $A\cap B=\emptyset$. If $a\in A$, then $a\notin B$, so $a\in A\setminus B$, and hence $A\subseteq A\setminus B$. The equality is shown by applying property 1. Next suppose $A\setminus B=A$. If $a\in A$, then $a\in A\setminus B$, so $a\notin B$, which means $A\subseteq B^{\complement}$, or $A\cap B=\emptyset$. ∎

5. 5.

$A\setminus\emptyset=A$ and $A\setminus A=\emptyset=\emptyset\setminus A$.

###### Proof.

The first equation follows from property 4 and the last two equations from property 3. ∎

6. 6.
 $A\setminus(B\cap C)=(A\setminus B)\cup(A\setminus C)\qquad\mbox{ and }\qquad A% \setminus(B\cup C)=(A\setminus B)\cap(A\setminus C).$
###### Proof.

These laws follow from property 2 and the de Morgan’s laws on set complement. For example, $A\setminus(B\cap C)=(A\setminus B)\cup(A\setminus C)=A\cap(B\cap C)^{% \complement}=A\cap(B^{\complement}\cup C^{\complement})=(A\cap B^{\complement}% )\cup(A\cap C^{\complement})=(A\setminus B)\cup(A\setminus C)$. The other equation is proved similarly. ∎

7. 7.

$A\setminus(A\cap B)=A\setminus B=(A\cup B)\setminus B$.

###### Proof.

The first equation follows from property 6: $A\setminus(A\cap B)=(A\setminus A)\cup(A\setminus B)=A\setminus B$ by property 5. Next, $(A\cup B)\setminus B=(A\cup B)\cap B^{\complement}=(A\cap B^{\complement})\cup% (B\cap B^{\complement})=A\cap B^{\complement}=A\setminus B$, proving the second equation. ∎

8. 8.

$(A\cap B)\setminus C=(A\setminus C)\cap(B\setminus C)$.

###### Proof.

Using property 2, we get $(A\cap B)\setminus C=(A\cap B)\cap C^{\complement}=(A\cap C^{\complement})\cap% (B\cap C^{\complement})=(A\setminus C)\cap(B\setminus C)$. ∎

9. 9.

$A\cap(B\setminus C)=(A\cap B)\setminus(A\cap C)$.

###### Proof.

$(A\cap B)\setminus(A\cap C)=(A\cap B)\cap(A\cap C)^{\complement}=(A\cap B)\cap% (A^{\complement}\cup C^{\complement})=((A\cap B)\cap A^{\complement})\cup((A% \cap B)\cap C^{\complement})=(A\cap B)\cap C^{\complement}=A\cap(B\cap C^{% \complement})=A\cap(B\setminus C)$. ∎

10. 10.

$(A\setminus B)\cap(C\setminus D)=(C\setminus B)\cap(A\setminus D)$

###### Proof.

Expanding the LHS, we get $A\cap B^{\complement}\cap C\cap D^{\complement}$. Expanding the RHS, we get the same thing. ∎

11. 11.

$(A\setminus B)\cap(C\setminus D)=(A\cap C)\setminus(B\cup D)$.

###### Proof.

Starting from the RHS: $(A\cap C)\setminus(B\cup D)=((A\cap C)\setminus B)\cap((A\cap C)\setminus D)=(% A\setminus B)\cap(C\setminus B)\cap(A\setminus D)\cap(C\setminus D)=(A% \setminus B)\cap(C\setminus D)$, where the last equality comes from property 10. ∎

Remarks.

1. 1.

Many of the proofs above use the properties of the set complement. Please see this link (http://planetmath.org/PropertiesOfComplement) for more detail.

2. 2.

All of the properties of $\setminus$ on sets can be generalized to Boolean subtraction (http://planetmath.org/DerivedBooleanOperations) on Boolean algebras  .

Title properties of set difference PropertiesOfSetDifference 2013-03-22 17:55:35 2013-03-22 17:55:35 CWoo (3771) CWoo (3771) 7 CWoo (3771) Derivation msc 03E20